2011
DOI: 10.1186/1744-9081-7-8
|View full text |Cite
|
Sign up to set email alerts
|

Facial and semantic emotional interference: A pilot study on the behavioral and cortical responses to the dual valence association task

Abstract: BackgroundIntegration of compatible or incompatible emotional valence and semantic information is an essential aspect of complex social interactions. A modified version of the Implicit Association Test (IAT) called Dual Valence Association Task (DVAT) was designed in order to measure conflict resolution processing from compatibility/incompatibly of semantic and facial valence. The DVAT involves two emotional valence evaluative tasks which elicits two forms of emotional compatible/incompatible associations (fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 92 publications
4
23
0
1
Order By: Relevance
“…Rather, we found a bilateral effect for faces, which was in accordance with fMRI [50] and other ERP data [51]. Moreover, the combined pattern of valence and stimulus type replicates similar work employing the DVT [3], [22], [28] and their association with ToM [3].…”
Section: Discussionsupporting
confidence: 92%
“…Rather, we found a bilateral effect for faces, which was in accordance with fMRI [50] and other ERP data [51]. Moreover, the combined pattern of valence and stimulus type replicates similar work employing the DVT [3], [22], [28] and their association with ToM [3].…”
Section: Discussionsupporting
confidence: 92%
“…The Emotion Recognition Task (ERT) is a face and word recognition task adapted from previous studies (Hurtado et al, 2009; Ibáñez et al, 2010, 2011; Petroni et al, 2011). This cognitive function has been thought of as a building block of social cognition (Green et al, 2008; Kurtz and Richardson, 2011; Pinkham et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…In support to this notion, the recognition of basic features (i.e., perceptual) carrying primary emotional information has been considered a fast and automatic process (Pratto and John, 1991; Öhman et al, 2001) responsible for programing and executing social responses (Fazio and Olson, 2003). This view has emerged from the use of experimental tasks designed to evaluate emotion recognition of faces (Heuer et al, 2007; Hurtado et al, 2009; Luo et al, 2010; Ibáñez et al, 2011, 2014; Petroni et al, 2011; Zhang et al, 2014) or words (Schacht and Sommer, 2009; Ibáñez et al, 2014). Petroni et al (2011) found that the recognition of face valence is associated to the ability to read others' intentions.…”
Section: Introductionmentioning
confidence: 99%
“…The DVT [39], [46][48] is an adaptation of the Implicit Association Task designed specifically for ERP measurements [40]. The DVT assesses the emotional valence (positive or negative) of faces and words.…”
Section: Methodsmentioning
confidence: 99%
“…To address this question we chose an ERP design based on a modified version of the dual valence task (DVT) [39], [40]. Participants had to classify stimuli according to its emotional valence (positive or negative).…”
Section: Introductionmentioning
confidence: 99%